Epidemiological accountability: philanthropists, global health and the audit of saving lives. Issue 1 (2nd January 2018) - Reubi, David
Abstract: There have been concerns about the recent private turn and re-emergence of philanthropies in world health, with many worrying about philanthropies' perceived lack of transparency and accountability. In contrast, I argue that while the private turn might have led to a decline in democratic or public accountability, it did not bring an end to all forms of accountability. Specifically, I suggest that philanthropists' involvement in global health has led to the spread of another, new form of accountability: epidemiological accountability. The latter is a combination of two regimes of expertise and practices hitherto kept separate: audit and epidemiology. To substantiate this argument, I draw on my research on the Bloomberg Initiative – a global effort to reduce tobacco use spearheaded by the Bloomberg and Gates foundations.